A Comparative Study of Occupational Safety and Health (OS&H) Regulations in United States, United Kingdom, Australia, South Africa, and Oman. Issue 3 (1st November 2022) - Umar, Tariq; Umeokafor, Nnedinma; Honnur Vali, Mohamed Shaik; Zia, Asad
Abstract: This article identifies the gaps in OS&H regulations in Omani construction using a critical review and analysis of relevant literature. Four countries United States of America (USA), United Kingdom (UK), Australia (AUS), and South Africa (SA) were then compared to Oman in relation to selected regulations. The study reveals fall from a height is one of the main causes of accidents in different sectors in Oman however there are no specific regulations that cover this cause of accidents in detail. The only regulation which applies to the "fall from a height" is the regulation of OS&H, issued by the Ministry of Manpower. Overall, the whole regulations applicable in Oman shows that although the term fall, appear several times in the regulation, the full spectrum of the fall protection is not covered in detail. The provision of chemical hazards in Omani regulations is not of the standards as adopted in the USA, UK, AUS, and SA. There is limited information for the regulated to support adequate compliance. While the term "scaffolding" was not found in the current regulations enforced in Oman, the term "ladder" was, however, used at five different instances in the regulations which obviously cannot substitute the scaffolding.